Perfil epidemiológico de câncer de cabeça e pescoço e o emprego de novas tecnologias no tratamento - Mesquita, Bárbara Freitas Freire (2016)
Background and Purpose: Head and neck cancer includes cancers originate in the oral cavity, oropharynx and larynx. The most common treatments are surgery, radiation and chemotherapy, and many adverse effects of the latter are known. Currently, we seek new technologies to improve the prognosis combined with reduced side effects. Health technologies are classified into hardware and software. The hardware technologies include artifacts such as tools and drugs. Software technologies include social tools, using relationship technologies as production contract, reception and care. This study aimed to describe the epidemiological profile of patients with CCP and analyze the importance of the use of new technologies hardware and software looking for improvements in the treatment efficiency and the quality of life. Methods: We conducted a study in 273 patients with CCP's Hospital Santa Rita de Cássia in Vitória-ES, the data was collected from 2012 to 2015. Were obtained staging data and tumor location, history of alcohol and tobacco, in addition to gender and age variables, and anthropometric and blood pressure measurements. Data were obtained from interviews, evaluations on the patient and analysis of records. Data were collected before and after treatment. The data were presented as mean ± SD and frequency. Chi square test were applied, Fisher's exact test, Wilcoxon and Mann Whitney test, in addition to Spearman. SPSS software was used (Statistical Package for Social Sciences), and Prism. The value of p <0.05 was considered significant. Results: More than 82% of patients are men and the average age of diagnosis is 59 years. Most of the patients had advanced stage. The most affected site was the oral cavity, and the treatment, half of the patients underwent chemotherapy and more than 2 \ 3 underwent radiotherapy and 38% for surgery. Most patients remain smokers and \ or alcoholic after diagnosis. Over 71% of individuals who smoke and \ or drink, had advanced stage. Smokers had a body mass index (BMI) less than nonsmokers, both before and after treatment. BMI of smokers and drinkers was lower than both abstainers. After treatment, there was significant reduction in mean arterial pressure. 9 Conclusion: We found that most individuals remain after the tobacco prognosis and a low BMI is associated with an advanced stage of the disease. The patient receiving treatment and remains smoker and \ or alcoholic substantially reduces its chances of remission, moreover, the loss of weight resulting from the adverse effects of smoking and also maintenance and alcoholism can lead to a worse prognosis. Combine application software technology proves to be as important as the use of hardware technology. At the end of this work are proposed simple actions to mitigate the side effects and enhance the therapeutic effect on this profile, in order to increase the capacity of the individual to receive and respond positively to treatment.